The Model of Coals Production in Indonesia - Dara Puspita Anggraeni; Dwi Noorma Putri (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2021)
The purpose of this research is to model the production of coals in Indonesia. The model used in this research is multiple linear regression. The independent variables in this model are the time(w) and the export (eb), while the dependent variable is the production of coals in Indonesia. The data used is the national export and production in 2012 until 2019. The best model obtained is prodi = -4,475* 1010+ 2,216*107 *wI + 1,649 * bei + This model has a MAPE of 5,27%. In this model time and export have explained 71,72 % of the independent variable that took effect from the production of coals in Indonesia.